LEADERSHIP MANAGEMENT OF EDUCATION AND PERSONALITY LEADERS OF INDUSTRIAL REVOLUTION 4.0 - Demina Demina; Zulmuqim Zulmuqim; Marhen Marhen; Syaiful Marwan (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
The industrial revolution 4.0 opened the eyes of every leader to fundamentally change, in every aspect of life. Changes and effects of the 4.0 revolution on education, progress and improvement in the quality and personality of its leaders. The development of science and technology undeniably influences the process of school organization in producing outputs that are ready to compete in the world of big data and discruptions. Responding to the challenges of the digital age, leaders need to prepare capable and skilled human resources, able to solve problems, communicate and collaborate with all lines. Teachers must get out of the mindset and safety zone for the learning process in an all-digital era and the principal is prepared externally and internally to adjust to the development of the industrial era 4.0 and distribution. The leader's personality is the total ethical appearance in leading and communicating and socializing with members of the organization.